Legal Issues Concerning the Transsexual Community in Malaysia - Thambapillay, Sridevi (Journal of Malaysian and Comparative Law, 2007)
Transexuality has been considered by many a phenomenon of the late 20th century when functions of the hormones began to be understood and surgical options became technically possible. The word was probably popularised in the late 1940s and 1950s by Dr Harry Benjamin, an American psychiatrist. Transsexuality is a gender identity disorder in which there is strong cross-gender identification. The purpose of this paper is to examine three legal issues (though there are many more) concerning the rights of transsexuals in Malaysia, namely, right to change gender status in the National Registration Identification Card (MyKard), right to marry in chosen or acquired gender, and right to adopt a child.